Alishir Navai’s Religious and Scholarly Works - Binnatova, Ulvi (Scholarya Demo Journal of Ruby, 2020)
Alishir Navai achieved recognition as a profound scholar, theoretician and even a facilitator of the Shariah science and Sufism. He was the first person to familiarize Turkic world with Islamic teachings and to teach Turkish to Islamic people. His works such as Munojot, Hadith-arbain, Nazm ul-Javohir, Siroj ul-Muslimin, Mahbub ul-Qulub, Lison ut-Tayr, Risolai tiyr-Andohtan were relevant both in their own time and today. Munojot (Praying to God) is composed of expressions that appeal to God, a manifestation of feelings in beautiful content and expression. The language of Munojot goes deep into the spiritual senses instilling in people the satiety of passion and humanistic feelings. Knowing that philosopher Abdurrahman Jamy was writing his Hadith-arbain, Alishir Navai overestimated his master’s decision and got his permission to translate this work to Chagatai Turkic language. Thus, working on “Hadith-arbain” Alishir Navai rewrote the work in the same year, in the same form, but in different style which consisted of couplets of 4 lines. The hadiths dedicated to the Prophet led to the writing of the meaning and essence of the hadiths, first in Arabic and then Turkish. Nazm alJavohir has an ancient religious and historical plot with moral values. The work can be evaluated as a sign of love and respect for one of the first caliphs of Islam hz. Ali. In this part of our research, we discuss the religious and scholarly works of Alishir Navai (especially the content and interpretation of Munojot, HadithArbain and Nazm ul-Javohir).